Development of Educational Game "Arabic Muslim Adventure" Based on Construct 2 Application to Improve Vocabulary Mastery - Hawalia Hastani; Asep Sopian; Shofa Musthofa Khalid (Taqdir, 2024)
In the digital era, teachers must innovate to create interactive learning media that can increase student interest in learning. Learning that is only focused on textbooks is monotonous. This study aims to develop an educational game media, Arabic Muslim Adventure (AMA), on vocabulary learning, test the feasibility, and determine the student's response to the AMA game. This research method is Research and Development (RnD), which refers to the 4D model. The results stated that the feasibility of the AMA game included very feasible criteria with a percentage of media experts at 97.64%, material experts at 97.14%, and learner responses with 24 respondents at 89% with a very feasible category. It can be concluded that the educational game "Arabic Muslim Adventure" is feasible and gets a good response from users, which can be applied to vocabulary learning.